Operando observation of analog resistance change in a buried metal/oxide interface by a laser-excited photoemission electron microscope. (1st October 2022) - Okuda, Y.; Kawakita, J.; Taniuchi, T.; Shima, H.; Shimizu, A.; Naitoh, Y.; Kinoshita, K.; Akinaga, H.; Shin, S.
Abstract: This study demonstrated our successful visualization of the non-volatile analog resistance changes in a metal/oxide/metal sandwiched structure. The resistance change has been intensively studied and practically utilized in the IoT devices, such as resistive random access memory and resistive analog neuromorphic device. Real-time observation technique of device operation ( operando observation technique) by laser-excited photoemission electron microscopy (Laser-PEEM) enabled the visualization. The operando observation showed that the signal intensity of Laser-PEEM changed over the whole of the device area with the analog resistance changes. It is sufficiently certain that the change in signal is due to the creation and repair of oxygen vacancies throughout the device area, because the signal intensity reflects the number of electrons near the Fermi level. Considering the results of this study, we conclude that the analog resistance change depends on the device structure and oxygen vacancy concentration in metal/oxide junctions, which are controllable determinants of the device operation.